Analysis Of Bottom Service Ability In Volley Ball Learning In Class Ix Students At Seluma 12 Negeri Junior High School - Trismayuni Trismayuni; Feby Elra Perdima; Supriyanto Supriyanto (Sinar Sport Journal, 2021)
This study aims to: determine the ability of students to do the bottom serve in volleyball learning in class IX students at SMP Negeri 12 Seluma. The method used in this research is descriptive quantitative method. The sample in this study amounted to 20 students. The instrument in this research is in the form of a lower service ability test. Based on the results of the study, it can be seen how much the students' ability in performing the bottom service for class IX students at SMP Negeri 12 Seluma as a whole is those who have the bottom service in the very good category, namely 0 people (0%), and those who have the bottom service in the good category namely 10 people (50%), and those who have lower service in the medium category are as many as 10 people (50%), and class IX students of State Junior High School 12 Seluma who have service under the less category are 0 people (0%), and those who have service under the category of very less are 0 people (0%).